Dextran-based hydrogel containing chitosan microparticles loaded with growth factors to be used in wound healing - Ribeiro, Maximiano José Prata (2018)
Skin injuries are traumatic events, which are seldom accompanied by complete structural and functional restoration of the original tissue. Different strategies have been developed in order to make the wound healing process faster and less painful. In the present study in vitro and in vivo assays were carried out to evaluate the applicability of a dextran hydrogel loaded with chitosan microparticles containing epidermal and vascular endothelial growth factors, for the improvement of the wound healing process. The carriers' morphology was characterized by scanning electron microscopy. Their cytotoxicity profile and degradation by-products were evaluated through in vitro assays. In vivo experiments were also performed to evaluate their applicability for the treatment of skin burns. The wound healing process was monitored through macroscopic and histological analysis. The macroscopic analysis showed that the period for wound healing occurs in animals treated with microparticle loaded hydrogels containing growth factors that were considerably smaller than that of control groups. Moreover, the histological analysis revealed the absence of reactive or granulomatous inflammatory reaction in skin lesions. The results obtained both in vitro and in vivo disclosed that these systems and its degradation by-products are biocompatible, contributed to the re-establishment of skin architecture and can be used in a near future for the controlled delivery of other bioactive agents used in regenerative medicine.